Gemogenovatucel-T (Vigil) Immunotherapy as Maintenance in Frontline Stage III/IV Ovarian Cancer (VITAL): A Randomized, Double-Blind, Placebo-Controlled, Phase 2b Trial. Issue 3 (March 2021) - Rocconi, Rodney P.; Grosen, Elizabeth A.; Ghamande, Sharad A.; Chan, John K.; Barve, Minal A.; Oh, Jonathan; Tewari, Devansu; Morris, Peter C.; Stevens, Erin E.; Bottsford-Miller, Justin N.; Tang, Min; Aaron, Phylicia; et al.
Abstract : (Abstracted from Lancet Oncol 2020;21:1661–1672) Standard-of-care treatment for stages III and IV newly diagnosed ovarian cancer involves primary debulking surgery followed by adjuvant paclitaxel and carboplatin or neoadjuvant chemotherapy with interval debulking surgery. Despite this protocol commonly resulting in complete remission, approximately 75% of patients will relapse within 2 years.